INOVASI PENGELOLAAN PROGRAM LITERASI MELALUI KEMITRAAN PENDIDIKAN DI SD NEGERI SAGENA KECAMATAN POTO TANO - Subki, S; Rahayu, Sri (Samalewa: Jurnal Riset & Kajian Manajemen, 2025)
This study aims to describe and analyze the management of literacy programs through educational partnerships at SDN Sagena. The research focus includes school policies, program innovations, the roles of stakeholders, as well as the impacts and challenges in literacy implementation. The research methodology employs a Mixed Methods approach, consisting of quantitative research with a quasi-experimental design and inferential analysis using the independent samples t-test to compare learning outcomes between the group receiving the literacy program treatment and the conventional learning group. For the qualitative component, data were collected through participant observation, in-depth interviews with the principal and teachers, and documentation studies. The results show that SDN Sagena has successfully integrated the literacy program into school policy through innovative programs named "SERASI" (Tuesday Wednesday Literacy) and "Literasi Bahari" (Maritime Literacy). This innovation utilizes the local context of the coastal community to increase the relevance of reading materials for students. The success of this program is supported by strategic partnerships with various external parties, such as the West Sumbawa Regency Education and Culture Office, JARI Foundation, Laskar Cinta Alam Community, and the Regional Library. The impact of this program is reflected in the increase in students' literacy scores, reaching an average of 81.20 in the experimental class compared to 75.54 in the regular class. Despite facing challenges such as limited human resources and coordination time, the school was able to overcome them through intensive parental involvement and home visit programs.